(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2023)
In order to gain illicit benefits or abuse power for one’s own benefit, corruption is a type of dishonesty or a criminal offense committed by a person or organization in a position of authority. This study examined the effect of corruption on achievement of construction project goals. This study collected data through the use of structured questionnaire that were administered to registered professionals in Ondo State. The target population comprises of Quantity Surveyors, Architects, Builders, and Engineer. Sixty-one questionnaires were administered; fifty questionnaires were retrieved from professionals. The data retrieved were analyzed using descriptive statistics, mean score response analysis frequency and percentages. The study concluded that the three major effect of corruption on achievement of construction project are: increase in cost of materials, high cost of the construction project as results of inflated price of bill of quantities and un-realistic claims during the course of execution of the project, creation of monopoly and also it was concluded that corruption is having major effects on cost more than on quality, client’s satisfaction, time, safety. Moreover, the study recommends that corruption should be eradicated in order to prevent increase in the cost of materials, high cost of the construction project as results of inflated price of bill of quantities and un-realistic claims during the course of execution of the project, creation of monopoly.